2008
DOI: 10.1021/es702882g
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Triclosan and Evidence for Reductive Dechlorination of Triclocarban in Estuarine Sediments

Abstract: The biocides triclosan and triclocarban are wastewater contaminants whose occurrence and fate in estuarine sediments remain unexplored. We examined contaminant profiles in 137 Cs/ 7 Be-dated sediment cores taken near wastewater treatment plants in the Chesapeake Bay watershed (CB), Maryland and Jamaica Bay (JB), New York. In JB, biocide occurrences tracked the time course of biocide usage and wastewater treatment strategies employed, first appearing in the 1950s (triclocarban) and 1960s (triclosan), and peakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
163
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 51 publications
15
163
2
Order By: Relevance
“…The background residuals are likely coming from both the aged biosolids and dredge sediment and the biosolids used for application in this experiment. Previously, TCC has been detected in sediment with concentrations varied from 0.7-1.6 mg g À 1 (Miller et al, 2008) and in the biosolids used for application in this study (13.33 mg g À 1 , Wu et al, 2010a). After harvest, the concentrations of CBZ dropped 21.5% and 39.5% in soils with radish and tomato, respectively.…”
Section: Resultsmentioning
confidence: 65%
“…The background residuals are likely coming from both the aged biosolids and dredge sediment and the biosolids used for application in this experiment. Previously, TCC has been detected in sediment with concentrations varied from 0.7-1.6 mg g À 1 (Miller et al, 2008) and in the biosolids used for application in this study (13.33 mg g À 1 , Wu et al, 2010a). After harvest, the concentrations of CBZ dropped 21.5% and 39.5% in soils with radish and tomato, respectively.…”
Section: Resultsmentioning
confidence: 65%
“…The weight contents of single TCS or TCC, or both together in the formulas of these products usually range from 0.1% to 2% (Chalew and Halden, 2009). It is reported that the combined annual consumption of TCS and TCC exceeds 600 tons in the United States (Miller et al, 2008), of which TCC usage is estimated to be 227e454 tons (Halden and Paull, 2005). In the European Union, the quantity of TCS used within the region was reported to reach approximately 450 tons for the year 2006 (EC, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of published studies, triclosan was reported in over 50% of all surface waters with a median concentration of approximately 50 ng/L [3]. It has been found in sediment cores dating back to the mid1960s at concentrations up to 800 mg/kg [4,5]. Concentrations of triclosan are generally higher toward core surfaces, indicating a recent increase in deposition [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found in sediment cores dating back to the mid1960s at concentrations up to 800 mg/kg [4,5]. Concentrations of triclosan are generally higher toward core surfaces, indicating a recent increase in deposition [4,5]. In addition to its persistence in sediments, triclosan has been shown to degrade to a dioxin in sunlight [6][7][8].…”
Section: Introductionmentioning
confidence: 99%